Innovation in cryotherapy after thirty years research in Poland - Łysień, Anna Monika; Mikrut, Grzegorz; Smykla, Agnieszka (Journal of Education, Health and Sport, 2019)
Year (2019) is the thirtieth of the opening of the first low-temperature chamber in Poland, is celebrated. This anniversary is a great occasion to recapitulation and evaluate our experince regarding cryogenic temperatures anhibition and present how this method of treatment has developed over the last 30 years. Cryotherapy became one of the most basic and modern therapeutic methods not only in physical medicine. Cryostimulation in new areas of life and as a form of thermal stimulation and assessment of its impact on the human body, taking into account the differences between individual human areas.